Comparative Histomorphology of the Ovary and the Oviduct in Rabbits and Pigeons - Ishaya, Helga Bedan; Omaga, Imelda; Dibal, Nathan Isaac; Attah, Martha Orendu O. (Journal of Morphological Sciences, 2018)
Introduction Knowledge of the evolutionary relationship between different classes of vertebrates can be obtained through a comparative study of their structures, forms, functions, and of the mode of development of the structures. Birds and mammals are vertebrates with different modes of reproduction, that is, oviparity in birds and viviparity in mammals. The aim of the present study is to compare the histomorphology of the ovaries and of the oviducts/uterine tubes in rabbits and pigeons. The present study highlights the histological and morphological differences that bring about the production of eggs in birds and the production of fully developed fetuses in mammals.Materials and Methods Five rabbits and five domestic pigeons were anesthetized with chloroform and sacrificed. The ovaries and the oviducts/uterine tubes were dissected and fixed in Bouin fluid and processed for a light microscopic study.Results The result showed paired ovaries and uterine tubes in rabbits that unite at the isthmus to form a single uterus that opens into the vagina, with only the left ovary and oviduct appearing as a compact body with distinct infundibulum, magnum, isthmus, uterus and vagina in pigeons. Photomicrographs of the ovaries of rabbits showed parenchyma cells with primary follicles, while the ovaries of pigeons showed developing follicles and yolk granules. Both the oviducts of rabbits and of pigeons showed a highly folded mucosa with a thick muscular wall.Conclusion The differences observed in the structures of the ovaries and of the oviducts of rabbits and pigeons might be due to their different reproductive functions in parturition (viviparity and oviparity, respectively).
Keywords: histomorphology; rabbit; pigeon; uterine tube; oviduct and ovary